(untitled) (Medicine Today, 2017)
This prospective study was conducted in the department of pediatric surgery, BIRDEM General Hospital and other Private Hospital in Dhakato evaluate the morphological parameters after orchiopexy in Undescended testis (UDT). Fifty five children of cryptorchidism in the age group of 6 months to12 years were included in the study from September 2012 to March 2017. Patients’ clinical characteristics, age at the time of orchiopexy, pre-operative ultrasonogram finding and intraoperative findings were recorded. On follow up postoperative complications and scrotal ultrasonogram findings were also recorded. Total 45 patients received regular ultrasound follow-up in next 6 months. Testicular length, width, position of the testes and any abnormal findings were documented. The testicular volume was then calculated with Hansen formula:Testicular volume= length (L) x width (W)2 x 0.52. The mean age at operation was 4.15 years. Sixty eightpercent of undescended testes were palpable, 97% of which could be initially placed in the scrotal position by surgery. Ninety threepercent remained in the scrotum at 6-month follow up. In 32% of cases, the testes were impalpable, 47% were intra-abdominal and 15.7% were absent. Eighty seven percent of all impalpable testes could be placed in the scrotum. At 6 months follow up, only 69% were in the scrotal position. Eighteen percent of impalpable testes and 2.4% of palpable testes underwent atrophy. The volume of scrotalized testis increased significantly after orchiopexy though the volume of undescended testis was smaller than that of normal descended testis in all age subgroups and revealed a slow growing trend. Medicine Today 2017 Vol.29(1): 35-38